MATHEMATICS MEDIA INSTRUCTION-BASED ANDROID FOR X-GRADE SENIOR HIGH SCHOOL - Surya Amami Pramuditya; Muchamad Subali Noto; Rian Nazaruddin Azhar (Journal Of Educational Experts (JEE), 2018)
AbstractThis research is motivated by students' learning difficulties exponent material, and lack of media in the learning process. One solution to overcome this problem is by developing a valid media and practical learning. The purpose of this research is to develop the Android application as a mathematics computer-assisted instruction Role- Playing Game (RPG) on practical and valid exponent material. The research is the R & D (Research and Development) and a method used in developing the media is a simplified method becomes ADD from ADDIE (Analysis, Design, Development). Data used in this research is quantitative. The instruments used interview guides and questionnaires. Data collection technique was an interview, validation sheets, and sheets practicalities. Research results obtained instructional media on the exponent material. Based on the results of the validation performed by five expert validation, obtained by 96.83% with very valid criteria. While the results of the practicalities by nine students obtained 84.32% with very practical criteria. This shows that the media instruction as a learning medium can be used in the learning process exponent material.Keywords: Media Instruction, Android Apps, ADDIE, Exponent.